Analisis Faktor yang Mempengaruhi Stres Kerja Dosen Perguruan Tinggi Swasta: Analysis of Factors Affecting Work Stress of Private College Lecturers - Khasanah Khasanah; Soewarto Hardhienata; Sri Setyaningsih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
In the context of higher education, work stress is an important issue faced by lecturers; work stress is a challenge faced by lecturers in higher education and can have a negative impact on the quality of teaching and human resource development. This study aims to develop a constellation model of influence between variables that contribute to reducing the work stress of lecturers at XYZ Private Higher Education. The research method used is a combination of quantitative and qualitative approaches, including surveys, interviews, and path analysis, to identify the relationship between independent and dependent variables. In addition, this study applies the Scientific Identification Theory to Conduct Research in Education Management (SITOREM) method to find the optimal strategy for reducing the work stress of lecturers. The results of the study indicate that several variables have a significant influence on the level of work stress of lecturers, including workload, social support, job satisfaction, and work-life balance. High workload tends to increase stress, while social support from colleagues and leaders, as well as high job satisfaction, can reduce stress levels. SITOREM analysis found that job security policies, fairer workload management, and increased social support and welfare facilities can be strategic solutions to reduce the work stress of lecturers. The conclusion of this study confirms that optimizing positive factors such as social support, work anxiety, and work-life balance can effectively reduce lecturers' work stress. The implications of these findings are expected to be the basis for university policies to improve lecturers' welfare and quality.